Perselingkuhan Dalam Keluarga: Faktor Penyebab, Dampak Psikologis dan Strategi Pemaafan dalam Hubungan - Zavira Taskia Ramadhani; Ummu Maimunah; Ufthy Nur Fahrani; Syulmi Annisa; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ITTC INDONESIA, 2026)
Infidelity is a primary cause of family relationship breakdown and a major trigger for divorce, accounting for nearly 70% of cases in Indonesia. This study aims to identify the driving factors of infidelity, its psychological impacts on family members, and effective recovery strategies using a literature review approach. The method employed is a literature review of 30 scientific journal articles (national and international) published between 2016 and 2026. Findings indicate that infidelity is triggered by the interaction of internal factors, such as insecure attachment styles and sexual dissatisfaction, and external factors, including digital technology intrusion and workplace opportunities. The resulting impacts are systemic, encompassing psychological trauma (PTSD), depression, and decreased self-esteem for the betrayed partner, as well as emotional developmental disruptions in children. Nevertheless, family relationships have the potential for restoration through mechanisms of genuine forgiveness, the development of self-compassion, and professional interventions such as couple therapy. This study concludes that addressing infidelity requires a multidimensional approach that integrates the strengthening of individual commitment with the improvement of relational communication.